Cell cycle‐regulated PLEIADE/AtMAP65‐3 links membrane and microtubule dynamics during plant cytokinesis. (5th October 2016) - Steiner, Alexander; Rybak, Katarzyna; Altmann, Melina; McFarlane, Heather E.; Klaeger, Susan; Nguyen, Ngoc; Facher, Eva; Ivakov, Alexander; Wanner, Gerhard; Kuster, Bernhard; Persson, Staffan; Braun, Pascal; et al.
Summary: Cytokinesis, the partitioning of the cytoplasm following nuclear division, requires extensive coordination between cell cycle cues, membrane trafficking and microtubule dynamics. Plant cytokinesis occurs within a transient membrane compartment known as the cell plate, to which vesicles are delivered by a plant‐specific microtubule array, the phragmoplast. While membrane proteins required for cytokinesis are known, how these are coordinated with microtubule dynamics and regulated by cell cycle cues remains unclear. Here, we document physical and genetic interactions between Transport Protein Particle II (TRAPPII) tethering factors and microtubule‐associated proteins of the PLEIADE/AtMAP65 family. These interactions do not specifically affect the recruitment of either TRAPPII or MAP65 proteins to the cell plate or midzone. Rather, and based on single versus double mutant phenotypes, it appears that they are required to coordinate cytokinesis with the nuclear division cycle. As MAP65 family members are known to be targets of cell cycle‐regulated kinases, our results provide a conceptual framework for how membrane and microtubule dynamics may be coordinated with each other and with the nuclear cycle during plant cytokinesis. Significance Statement: Cytokinesis requires extensive coordination between cell cycle cues, membrane trafficking and microtubule dynamics. Here we document physical and genetic interactions between membrane (Transport Protein Particle II, TRAPPII tethering complex) and microtubule (microtubule‐associated proteins of the PLEIADE/AtMAP65 family) components of cytokinesis and use our results to outline a conceptual framework for their coordination during plant cytokinesis.